أثر إستراتیجیة التعلم المرتكز على المشكلة في مستویات بلوم ( فھم ومعرفة واكتشاف ) الأھداف السلوكیة للتحصیل المعرفي لمادة طرائق التدریس - المرحلة الثانیة لكلیة التربیة البدنیة وعلوم الریاضة - هدى عبد السميع عبد الله (الرياضة المعاصرة)
It is certain that choosing the pivot educational strategy on the problem is considered the ideal to limit the behavior purposes or aims and getting knowledge for the subject of leaching methods. It fulfills the required results and ensures the movement of positive learning in building the learner to know educations and new concepts by pivotting on the previous concepts which the research aim to be familiar. With the effect of the strategy of education which was the vipot on the problem in the concepting and knowing the behavior aims and the knowledgeable getting in the subject of teaching methods for the girl students who are in the second stage in the physical education college and the sciences of maths for girls . The zero supposition was put without existing differences which has evident statistics between the two trying groups who are studying by the educational strategy pivotting on the problem in getting knowledge and among the exacting group who study by classical traditional method .And the research society consists of (26) students from the second stage for the physical college and the sciences of maths for girls The resulted represented at finding existing differences having evident statistics between the two attempting and exaoting groups for the attempting groups in the further tests . The female prenoher recommends in the necessary familiars with the active learning strategy which are among them the strategy pivoted on round or about the problem for reaching positive result in different specialists